A Systematic Review of the Therapeutic Applications and Functional Benefits of Propolis - Ahmadi, Sayed Arif (Journal of Natural Sciences – Kabul University, 2025)
This study aims to provide updated information on the chemical composition, biological activity, and functional properties of propolis in the food and pharmaceutical industries. Propolis is a unique natural substance collected by honeybees from plant sources. It serves as a defensive material in the hive and possesses diverse biological activities with significant health benefits. The study adopts a systematic review approach, analyzing both national and international scientific sources. The findings indicate that propolis exhibits antioxidant, antibacterial, antiviral, antifungal, and antiparasitic properties. It has applications in vaccine production, cancer treatment, and the development of food, pharmaceutical, and cosmetic products. Owing to its bioactive compounds, propolis has attracted considerable attention across various industries and can play an important role as a valuable natural substance in promoting human health.